Impact of testosterone on trophoblast mitochondrial function - Parsons Aubone, Agata M., author; Chicco, Adam, advisor; Tesfaye, Dawit, committee member; Tjalkens, Ron, committee member (Colorado State University. Libraries, 2022)
Several pregnancy disorders involve placental abnormalities, including gestational diabetes mellitus (GDM) (2-10% of pregnancies), preeclampsia (PE) (6-8% of pregnancies), and polycystic ovary syndrome affects (PCOS) (6 to 15% of women in reproductive age), which not only has a negative impact on maternal health but can also lead to birth defects and postnatal health complications. These disorders commonly also present high levels of androgens in maternal blood, accompanied by placental insufficiency. The placenta in these pathologies presents morphological and physiological alterations, including in the trophoblast mitochondria. The placenta is a multifunctional, transient organ that mediates the transport of nutrients and waste to and from the fetus, gas exchange, and endocrine signaling to maintain maternal and fetal homeostasis. To facilitate these diverse and important functions and enable proper fetal growth and development, the placenta is highly metabolically active and consumes ~40% of the total oxygen. Oxygen is used for the synthesis of ATP in mitochondria, which in turn is mainly used for cholesterol transport and steroidogenesis. The placenta is well recognized as a hormone-synthesizing and secreting organ; however, studies revealed it is a target of these hormones as well and contains receptors for various steroid hormones including androgens. Placental androgen receptor (AR) is relevant in pregnancy disorders with elevated androgens such as GDM, PE, and PCOS. These are accompanied by placental pathologies that include mitochondrial adaptations that vary according to the stage of the pathology, and in advanced stages when levels of reactive oxygen species (ROS) become too high they can have detrimental effects on the placenta and can even lead to pregnancy loss. Of particular interest here is the recent observation that AR has been identified as a regulator of mitochondrial function in other tissues such as the prostate and cancer. The production of ROS and/or the decrease in antioxidant defenses are the main mechanisms underlying placental insufficiency in pathologies with elevated androgens. A better understanding of the regulation of androgen signaling in placental mitochondria will lead to new insights and opportunities to understand and treat disorders of pregnancy that affect a significant number of pregnant women. Studying the human placenta in vivo presents several complications, so it is necessary to use in-vitro models. There are several human trophoblast cell lines available, but none are perfect replacements for the original organ, rather each one has qualities that allow investigators to choose one best suited for their study. The overall goal of our studies is to investigate the role of AR signaling in trophoblast cell mitochondrial respiration. Our hypothesis is that AR signaling regulates mitochondrial oxygen consumption and ROS production. The first chapter will provide an overview on the role of androgens in placental physiology and pregnancy, and the role of mitochondria in trophoblast cell function. In the second chapter, we present studies aimed at characterizing mitochondrial respiration in existing placental cell lines and elucidating a possible role for AR signaling in mitochondria. Specifically, we first demonstrated the presence of AR in placental mitochondria. Next mitochondrial oxygen consumption and ROS production are characterized and compared using an Oroboros O2K oxygen respirometer in three well-known human (ACH-3P, BeWo, and Swan-71) and one immortalized ovine trophoblast cell (iOTR) line. Finally, ACH-3P cells are selected to test mitochondrial responses to testosterone, mimicking placental pathologies seen in GDM, PE, and PCOS. Our results revealed that both human ACH-3P and Swan-71 cells, as well as the sheep iOTR cells, demonstrated normal oxygen consumption and ROS production following the addition of selected complex protein substrates. Chronic testosterone treatment led to significant increased ROS production in ACH-3P cells, which correlates with what has been observed in term placentas of women with placental hyperandrogenism. In conclusion, the ACH-3P cell line is a good in vitro model to study placental mitochondrial respiration. Ultimately, the presented data provide new information regarding the possible role of AR signaling in placental mitochondria and will pave the way for future studies aimed at uncovering the mechanism of AR regulation of mitochondrial function in normal and abnormal pregnancies (discussed in Chapter 3).
Keywords: mitochondria; pregnancy; trophoblast; placenta; androgens; testosterone